THE PROCESSING OF THE ELLIPTICALLY POLARIZED SIGNAL IN RADAR STATIONS WITH DIGITAL SYNTHESIS OF THE ANTENNA APERTURE - P. E. Korneev (Научный вестник МГТУ ГА)
The processing of the elliptically polarized reflected signal in the Earth remote sensing systems makes it possible to obtain additional advantages when solving problems of recognition of the observable objects on the ground and under the ground. Full polarization reception implemented in radar stations with digital synthesis of the antenna aperture when remote sensing of the Earth increases the information content of such radars (the radar image of the investigated surface is detailed, the contrast of objects in the field of view is improved, and various negative effects of the image are minimized). The paper considers the quadrature processing of the reflected elliptically polarized signal in radar stations with digital synthesis of the antenna aperture in the mode of lateral survey of the terrestrial (water) surface. The processing of the reflected signal using the methods of radio polarimetry opens new possibilities for such radars while solving problems of remote sensing of the surface and recognition of radar targets. In addition, radar stations with digital synthesis of the antenna aperture with processing of an elliptically polarized signal have a higher interference immunity compared to radars, where a linearly polarized signal is processed. In the article, mathematical modeling is performed in the part of demodulation of the in-phase and quadrature components of the trajectory signal when the geometric parameters of the polarization ellipse change. The obtained analytical expressions allow estimating the influence of the geometric parameters of the polarization ellipse on the trajectory signal being processed. It is analytically confirmed that the angle of ellipticity affects the energy characteristics, and the orientation angle of the polarization ellipse introduces an additional phase shift in the characteristics of the trajectory signal being processed. Not taking into account these nuances while designing digital units and systems of such radars can lead to the loss of all the benefits of processing an elliptically polarized signal. The paper presents a structural scheme of the polarization radar station with digital synthesis of the antenna aperture.